Compression at the Source for Digital Camcorders. (22nd May 2007) - Maor Maor, Nir Nir; Feuer Feuer, Arie Arie; Goodwin Goodwin, Graham C. Graham C.
Abstract : Typical sensors (CCD or CMOS) used in home digital camcorders have the potential of generating high definition (HD) video sequences. However, the data read out rate is a bottleneck which, invariably, forces significant quality deterioration in recorded video clips. This paper describes a novel technology for achieving a better utilization of sensor capability, resulting in HD quality video clips with esentially the same hardware. The technology is based on the use of a particular type of nonuniform sampling strategy. This strategy combines infrequent high spatial resolution frames with more frequent low resolution frames. This combination allows the data rate constraint to be achieved while retaining an HD quality output. Post processing via filter banks is used to combine the high and low spatial resolution frames to produce the HD quality output. The paper provides full details of the reconstruction algorithm as well as proofs of all key supporting theories.